On permeability and strength characteristics of lateritic soils / Mohammad Fadhli Ahmad - Ahmad, Mohammad Fadhli (1993)
This study is limited to laboratory investigation on the strength characteristics and permeability of lateritic soils.The testings carried out were CBR and MBR tests,direct shear strength test, air and water permeability tests.The purpose of this study is to examine the influence of confining pressure has on the strength characteristics of lateritic soils.This study also examine the influence of the degree of compaction on the shear strength value.In addition influence of compaction energy and water content on the air and water permeability are examined. The experimental program on strength characteristics and permeability using lateritic soils taken from construction site near ITM Shah Alam.Three different lateritic soils namely clayey sand, silt of low plasticity and clay of high plasticity were used.